Frontal Crash Injury Metrics Are Below Mandated Limits for a Spica Casted Child Dummy in Currently Available Restraints. Issue 5 (May 2020) - Collins, Angela C.; Caskey, Sean; Peck, Jeffrey B.; Walter, Norman; Atkinson, Theresa S.; Atkinson, Patrick J.
Abstract : Background: There is a paucity of data defining safe transport protocols for children treated with hip spica casting. Although restraint devices for casted children are available, all federally mandated testing uses a noncasted anthropomorphic test device (ATD or crash dummy). The purpose of this study was to evaluate current restraint options in simulated frontal crash testing using a casted pediatric ATD to determine injury risk to the head, cervical spine, chest, and pelvis. Methods: Using a 3-year-old ATD, dynamic crash sled tests simulating frontal crash were performed in accordance with government safety standards. The ATD was casted in a double-leg spica and the following restraint devices were tested: a seat designed for spica casted children, a restraint vest-harness, a traditional booster seat, and 2 traditional forward-facing car seats. Results: Although the presence of the cast increased many of the injury metrics measured, all seats passed current federal guidelines for the head and chest. No single seat performed best in all metrics. The greatest magnitude of neck loading and second-highest head injury criterion values were observed for the booster seat. The vest-harness produced the highest head injury criterion and the chest compression exceeded proposed federal limits. Conclusions: The results suggest safe transport in commercially available seats is possible with the child properly restrained in a correctly fitting seat. However, parents should not assume a child restraint system is appropriate for use just based on fit as, for example, seats with harnesses outperformed an easy to fit booster seat. Clinical Relevance: Each child and the position of the child's cast are unique and discharge planning involves consideration of safe transportation. Although this study suggests several seats used to transport spica casted children pass the federal head and chest injury prevention requirements, it is important to recognize that some children may still require emergency vehicle transport.